Improvement of Memory and Motivation in Language Learning in Primary Education through the Interactive Digital Whiteboard (IDW): The Future in a Post-Pandemic Period - Bautista Vallejo, José Manuel; Hernández-Carrera, Rafael M.; Moreno-Rodríguez, Ricardo; López-Bastias, José Luis (Sustainability, 2021)
This paper presents an analysis of the use of an interactive digital whiteboard (IDW) and a computer application called Action Manager (AM), with a sample of 158 sixth-grade students in primary education. Subsequently, a study was carried out with the main goal of testing the didactic functioning of AM and examining the validity of this application, in terms of motivation and the retention of both short and long-term memory when teaching foreign languages in primary education. In order to fulfil these objectives, we performed a positivist exploratory study based on a quantitative methodology combining qualitative aspects (qualitative evaluation) and quantitative aspects (questionnaires) as well as a descriptive method with a survey design. The data collection was performed using instruments, specifically the Extrinsic vs. Intrinsic Orientation Scale, to ascertain the motivational impressions of the students and two memory tests, the Test of Memory and Learning (TOMAL) and the Children's Memory Scale (CMS). Forty-five days later, the two memory tests were repeated to compare the results with the previous ones. After this experience, the results allowed us to conclude that the students demonstrated optimal memorization from a conceptual point of view, in addition to having improved their motivational impressions.
Keywords: interactive digital whiteboard; memory; motivation; language learning; ICT; JCR; Scopus